2006
DOI: 10.2151/jmsj.84a.151
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Study on Interactions Between Atmospheric Thermodynamic Structure and Cumulus Convection over the Tropical Western Pacific Ocean and over the Indochina Peninsula

Abstract: Interactions between the convective activity and the atmospheric thermodynamic structures are analyzed utilizing upper-air rawinsonde observations obtained by R / V Mirai, R / V Kaiyo, R / V Natsushima, of the Japan Agency for Marine-Earth Science and Technology (JAMSTEC) over the western tropical Pacific Ocean, and those over three GEWEX Asian Monsoon Experiment (GAME) stations: Chiang Mai, Non Khai, and Ubon Ratchathani. Special emphases are placed on understanding the correlation between convection and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
9
20
0
Order By: Relevance
“…Takayabu et al (2006) showed the existence of a significant meridional divergence around 500-600 hPa, which almost coincides with the diagnosed level of detrainment, in addition to the deep meridional cell of the local Hadley circulation over the western Pacific. In addition, Wu (2003) showed that shallow heating profiles effectively drive shallow circulations, which range from the surface to ;500 hPa.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Takayabu et al (2006) showed the existence of a significant meridional divergence around 500-600 hPa, which almost coincides with the diagnosed level of detrainment, in addition to the deep meridional cell of the local Hadley circulation over the western Pacific. In addition, Wu (2003) showed that shallow heating profiles effectively drive shallow circulations, which range from the surface to ;500 hPa.…”
Section: Introductionmentioning
confidence: 57%
“…Nolan et al (2007) show that shallow return flows have importance in terms of the moisture transport in and out of the ITCZ, so it is meaningful to understand the behavior of the largescale circulation over the eastern Pacific in detail. Note that the SMCs appear not only over the eastern Pacific but also over the central and western Pacific, Atlantic, Africa, and the Indian subcontinent (e.g., Takayabu et al 2006;Zhang et al 2006Zhang et al , 2008. In addition, SMCs are observed not only over ITCZ regions, which we will examine in this study, but also in monsoon heat low regions such as the West Africa monsoon region .…”
Section: Introductionmentioning
confidence: 92%
“…Therefore downdrafts from deep convection have to cause a large decrease of the y à e , (>20 K) at the middle level to generate the cumulus congestus. However since it is unrealistic, the evaporation effect of hydrometeors below the middle level is emphasized (e.g., Takayabu et al 2006). On the other hand, the small G below the middle level around the Baiu frontal zone is brought through latent heat release associated with convective activities, described above.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We then obtain a mean value of CAPE6 for all Baiu seasons from 1998 to 2006 (CAPE6-M), which is 350.3 J kg -1 . The thermodynamic conditions for an individual day are determined from the sign of the anomaly of CAPE6 from CAPE6-M. To calculate CAPE, the lowest level is selected for the starting level of the parcel since previous studies indicated that the diagnosed cloud base is not too sensitive to the selection of the air at 900 to 1000 hPa levels (Takayabu et al 2006), so that mostly 1000 hPa is selected. When the level of free convection (LFC) is not diagnosed, CAPE is set to zero.…”
Section: Methodsmentioning
confidence: 99%